MANAGEMENT INDICATORS OF GOOD INFRASTRUCTURE FACILITIES TO IMPROVE SCHOOL QUALITY - Siswanto, Edy; Hidayati, Dian (International Journal of Educational Management and Innovation, 2020)
Facilities and infrastructures in education are essential to improve the quality of the teaching and learning process in schools. Principals are responsible for managing facilities and infrastructures in schools. The implementation of learning to teach in schools will be subjected to obstacles when facilities and infrastructure are inadequate. The purpose of this research is 1) describing the importance of facilities and infrastructure in improving the quality of learning, 2) Knowing how to plan, manage, use and maintenance of facilities and infrastructure in schools, 3) indicators Management of good infrastructure for the improvement of School quality 4) school readiness in preparing facilities and infrastructure to support learning in the 4.0 era. The case study used in MTS Muhammadiyah Sidomulyo. The research used in this research is descriptive qualitative research. Data collection techniques using interviews, observation, and documentation. The results of the research show that the headmaster is planning in fulfilling facilities and infrastructure tailored to the level of needs each year. The planning will be known as management indicators of any infrastructure which is a good or most significant influence on the improvement of the quality of the school. Precisely the use of facilities and infrastructure can improve the quality of learning in Mts Muhammadiyah Sidomulyo. Damaged facilities and infrastructure will be given repairs. If no longer repaired, the school will apply for new procurement. All parties in the school must maintain existing facilities, and infrastructures to improve the quality of learning.